2020
DOI: 10.1007/s00167-020-05879-9
|View full text |Cite|
|
Sign up to set email alerts
|

Vancomycin-soaked autografts during ACL reconstruction reduce the risk of post-operative infection without affecting return to sport or knee function

Abstract: Purpose To compare return to sport and knee function 1 year after anterior cruciate ligament (ACL) reconstruction using autografts with and without vancomycin presoaking. Methods A case–control study based on a retrospective analysis of prospective data included athletes over the age of 16 operated from 2012 to 2018 for ACL reconstruction. There were two groups of patients due to a change in treatment protocols: Group 1 « without vancomycin » before November 2016 and Group 2 « with vancomycin» after this dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…All the studies included in this systematic review were level III studies [2][3][4]8,20,[22][23][24][25]28,30]. Two studies reported on the same patient population, with the followup study including a larger number of patients in the treatment group (vancomycin) and the same control group of the former study [23,28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the studies included in this systematic review were level III studies [2][3][4]8,20,[22][23][24][25]28,30]. Two studies reported on the same patient population, with the followup study including a larger number of patients in the treatment group (vancomycin) and the same control group of the former study [23,28].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, regarding infection, only 5 studies (4 m using only hamstring grafts) [2,8,23,28,30] reported the type of graft in infected patients, preventing the possibility of analyzing data on graft type differences. Three studies [3,4,28] included open procedures (collateral ligament repair/ reconstructions or extra-articular tenodesis) in the same surgical act as the ACL reconstruction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Jacquet et al 24 in a study using living donors found that presoaking of human semitendinosus grafts with vancomycin (5 mg/mL) does not alter their biomechanical properties at time zero. Until now, there have been no studies regarding long-term biomechanical effects of its use, however, Offerhaus et al 15 published a significant decrease of graft failure in patients with Vancomycin presoaked grafts and no increase in the rate of postoperative arthrofibrosis and subjective outcome scores compared to a control group without Vancomycin, and Bohu et al 20 found no differences in return to running and overall knee function with control patients. In addition, they found that more patients with Vancomycin presoaked grafts returned to their pre-injury sport compared to their control counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Bohu et al 20 conducted a study to compare return to sports and knee function one year after ACL reconstruction using autografts with and without Vancomycin presoaking. In this series, 79.3% of the patients were operated using a hamstring autograft.…”
Section: Available Studiesmentioning
confidence: 99%